PENERAPAN PAJAK PENGHASILAN YAYASAN KEAGAMAAN PADA YAYASAN EKA DHARMA DAUN TERATAI EMAS - Wijaya, Henryanto; Selvia Putri Patricia; Sheila Elita Nanang (Jurnal Serina Abdimas, 2025)
Yayasan Eka Dharma Daun Teratai Emas is a foundation that operates in the religious sector. Where there is still a lack of understanding of the tax aspects of religious foundations, this can lead to errors in income tax reporting. So in order to equip foundation administrators with tax insight, our PKM team from the Faculty of Economics and Business, Tarumanagara University will carry out outreach and training on the application of income tax for religious foundations. With this activity, it is hoped that religious foundations can carry out their tax obligations properly and correctly in accordance with the provisions of the applicable tax regulations. And you can also take advantage of tax incentives obtained by religious foundations. The solution we provide is to conduct an FGD (Forum Group Discussion) together with the foundation management to identify the problems in Yayasan Eka Dharma Daun Teratai. We found that socialization regarding the calculation of income tax on religious foundations is very necessary. Starting from explaining the taxation aspects of religious foundations, good recording or bookkeeping, preparing financial reports, and until calculating the income tax. Through these stages, it is hoped that we can produce good output by implementing the solutions offered. Not only the implementation of the above aspects, but supervision from the management of the foundation also needs to be carried out so that the implementation of the above can be carried out properly and correctly. Regular evaluation is also needed to increase the credibility of financial reports. So that in this way, Yayasan Eka Dharma Daun Teratai can report its income tax properly and be free from tax sanctions. ABSTRAK Yayasan Eka Dharma Daun Teratai Emas merupakan yayasan yang bergerak di bidang keagamaan. Dimana masih kurangnya pemahaman atas aspek perpajakan yayasan keagamaan dapat menimbulkan kesalahan dalam pelaporan pajak penghasilan. Sehingga dalam rangka memperlengkapi pengurus dengan wawasan perpajakan tersebut, tim PKM kami yang berasal dari Fakultas Ekonomi dan Bisnis Universitas Tarumanagara akan melaksanakan sosialisasi dan pelatihan penerapan pajak penghasilan bagi yayasan keagamaan. Dengan kegiatan ini diharapkan agar yayasan keagamaan dapat menjalankan kewajiban perpajakan dengan baik dan benar sesuai ketentuan peraturan perpajakan yang berlaku. Dan juga dapat memanfaatkan insentif perpajakan yang didapatkan oleh Yayasan keagamaan. Solusi yang kami berikan adalah dengan melakukan FGD (Forum Group Discussion) bersama dengan pengurus yayasan untuk mengidentifikasi permasalahan yang dialami. Kami menemukan bahwa sosialisasi mengenai perhitungan pajak penghasilan atas yayasan keagamaan sangat perlu untuk dilakukan. Dimulai dari penjelasan aspek perpajakan yayasan keagamaan, pencatatan atau pembukuan yang baik, pembuatan laporan keuangan, hingga perhitungan pajak penghasilan. Melalui tahapan tersebut diharapkan dapat menghasilkan output yang baik dengan menerapkan solusi yang ditawarkan. Tidak hanya penerapan aspek-aspek diatas, namun pengawasan dari pihak manajemen pengurus yayasan juga perlu dilakukan sehingga pelaksanaan hal diatas dapat dilakukan dengan baik dan benar. Evaluasi rutin juga diperlukan untuk meningkatkan kredibilitas laporan keuangan. Sehingga dengan demikian, Yayasan Eka Dharma Daun Teratai dapat melaporkan pajak penghasilannya dengan baik dan terbebas dari sanksi perpajakan.